Implementation of Archipelago Insights in Growing Attitude of Nationalism in Young Generations - Muhammad Naufal Rafif; Fatma Ulfatun Najicha (Department of Civic Education, 2022)
Globalization has brought various bad effects to Indonesia, one of which is Westernization. So, we need a point of view that can combat Westernization which is manifested in the form of Archipelago Insights. Even so, there are still many Indonesians who have not instilled the values of the Archipelago insight into their lives. As a result, their nationalism, especially their love for the homeland, will be lacking. Therefore, this research was conducted to identify why this event could occur, and then to help readers, especially the younger generation, to be able to recognize and understand the identity of the Indonesian people so as to instill the values of insight into the archipelago and an attitude of love for the homeland. This research is a compilation of findings from various sources, such as journals, articles, and books that discuss Archipelago Insights, globalization, nationalism, and so on which will then be discussed to show methods that can be used to increase nationalism. From the results of this study, nationalism can arise when there is a push from Wawasan Nusantara which provides a view of Indonesia through personality.